DEPOSITION THICKNESS AND ITS EFFECT ON CRITICAL SHEAR STRESS FOR INCIPIENT MOTION OF SEDIMENTS (Jurnal Teknologi (Sciences & Engineering), 2016)
There are evidences in existing literatures suggesting the incipient motion values for any particle size is substantially lower for rigid boundary condition as compared to loose boundary condition.  The objective of the current study is to determine the effect of sediment deposition thickness on the critical shear stress for incipient motion. Experimental works for incipient motion were carried out in a rectangular flume with varying sediment deposits thickness. Results showed that the sediment deposits thickness has effect on the critical shear stress at low sediment deposits thickness and the effect will slowly diminish as the sediment deposits thickness increases. Multiple linear regression analysis was performed on the experimental data to develop a new critical shear stress equation.  The best regression model has   value of 0.69;    value of 0.60;  value of 0.009 and Mallow’s  value of 3.00. The new equation appears to be more consistent as compared to existing incipient motion equations for rigid boundary condition by having 80% of the predicted data falls within the acceptable discrepancy ratio when tested with data from other authors. The new equation can be used to determine critical shear stress values for self-cleansing sewerage design and other related engineering applications